Ringing in the Common Love of Good: The United Farmers of Ontario in Lambton, Simcoe and Lanark Counties, 1914-1926 - Badgley, Kerry (McGill-Queen's University Press, 2000)
Founded in 1914, the United Farmers of Ontario (UFO) became a significant force in the province, winning the most seats in the 1919 provincial election and forming a governing coalition with the Independent Labour Party. The UFO and its companion organizations, the United Farmers Cooperative Company (UFCC) and the United Farm Women of Ontario (UFWO), flourished, achieving much of its success by challenging those who controlled the economic, political, and social structures in Ontario and advancing an alternative vision of democracy that sought to maximize citizen participation in the decision-making process. By the mid-1920s the UFO had gone into a period of decline from which it never recovered. The promise of equality hoped for by UFWO members never materialized and the UFCC, once a key component in the development of an alternative vision, began to focus more on profits than on politics. In Ringing in the Common Love of Good Kerry Badgley explores both the rise and the fall of the UFO, focusing on the Ontario counties of Lambton, Simcoe, and Lanark. He challenges the liberal-capitalist interpretation that the movement was nothing more than a group of impatient Liberals, as well as the Marxist view that the UFO consisted of self-interested independent commodity producers. Badgley argues that as the UFO broke free from hegemonic forces it developed alternative economic, political, and social visions, but that it was these same forces, combined with internal struggles and a conservative leadership, that ultimately resulted in the decline of the movement as a vehicle for democratic change in Ontario. --Publisher's description

Employment Equity Policy in Canada: An Interprovincial Comparison - Bakan, Abigail B.; Kobayashi, Audrey Lynn (Status of Women Canada, 2000)
Keywords: Canada; Discrimination in employment; Employment Government policy; Government policy; Minority women

A Square Deal for All: Historical Essays on Labour in Brandon - Black, Errol; Mitchell, Tom (Canadian Committee on Labour History, 2000)
The authors' careful analyses of labour and working-class organizations in Brandon [Manitoba] are aimed at reconstructing and disclosing aspects of the history of class and class relations. While other western Canadian cities, Winnipeg, for example, have received much deserved attention by historians, studies of other cities, such as Brandon, in the early 20th century help to provide a more well-rounded understanding of working-class life in Canada during this period. In the tradition of the new labour history Black and Mitchell pay close attention to the unique development of class relations in the community of Brandon, while placing that community in a broader, national context. This work includes a careful consideration of the working class in Brandon, the particular obstacles and challenges workers there faced, and makes an important contribution to our understanding of class relations in Canada. --Publisher's description
Keywords: History; Labor; Labor Manitoba Brandon History; Labor movement; Labor movement Manitoba Brandon History; Manitoba Brandon; Mouvement ouvrier Manitoba Brandon Histoire; Travail Manitoba Brandon Histoire; Travailleurs Manitoba Brandon Histoire; Working class; Working class Manitoba Brandon History

English Immigrant Voices: Labourers' Letters from Upper Canada in the 1830s - Cameron, Wendy; Maude, Mary McDougall; Haines, Sheila (McGill-Queen's University Press, 2000)
Emigrants sent by the Petworth Emigration Committee were part of a wave of rural workers in the 1830s whose immigration to Upper Canada was sponsored by English parishes and landlords. Their letters written or dictated to family and friends, leave us a rare first-hand view of the immigrant experience from a working-class perspective. Collected from published, archival, and private sources, these letters place the Petworth immigrants in the context of their times and challenge the image of English immigrants to 1830s Upper Canada as officers and gentlewomen. Wendy Cameron, Sheila Haines, and Mary McDougall Maude have carefully annotated the letters to sketch the stories of individual writers, link letters by the same author or members of the same family, and explore the connections between writers. What eventually happened to some of the writers is also revealed in this engaging collection. English Immigrant Voices provides a valuable insight into the rural poor and their experiences in emigrating to a new land. --Publisher's description
Keywords: 19th century; British; Correspondence; History; Immigrants; Ontario; Working class

Canadian Marxists and the Search for a Third Way - Campbell, J. Peter (McGill-Queen's University Press, 2000)
The triumphs and failures of four Canadian Marxists who advocated organization and education rather than armed struggle in the revolutionary overthrow of capitalism and the creation of socialism. Literature on Marxist socialists in Canada has usually been written by those within the social democratic or Marxist-Leninist traditions and has generally failed to break free of the political biases of the defenders of these traditions. Canadian Marxists and the Search for a Third Way steps outside these approaches to appraise early Canadian Marxists on their own terms. Peter Campbell argues that their Marxism was a changing and evolving product of their intellectual development and day-to-day interaction with the Canadian working class. It was a dynamic, theoretical system that provided a "third way" to look at Marxism, a revolutionary socialism that rejected violence in favour of the broadest organization and education of the working-class majority. Focusing on four individuals, Canadian Marxists and the Search for a Third Way describes the lives and ideas of Ernest Winch, Bill Pritchard, Bob Russell, and Arthur Mould and examines their efforts to put their ideas into practice. Campbell begins by looking at their childhoods in Great Britain, particularly their religious upbringing. He considers their family life, their attitudes toward women and ethnic minorities, what they were reading, and what effect that reading had on their theory and practice. He describes their lives as labor leaders and advocates of socialism, revealing how tenaciously, in an increasingly hierarchical, bureaucratized, and state-driven capitalist society, they held to the idea that socialism must be created by the working class itself. This is a unique look at four Canadian Marxists and their struggle to create an educated, disciplined, democratic, mass-based movement for revolutionary change. --Publisher's description

Click, Clack, Moo: Cows That Type - Cronin, Doreen; Lewin, Betsy (Simon & Schuster Books for Young Readers, 2000)
Farmer Brown has a problem. His cows like to type. All day long he hears Click, clack, MOO. Click, clack, MOO. Clickety, clack, MOO. But Farmer Brown's problems REALLY begin when his cows start leaving him notes.... Doreen Cronin's understated text and Betsy Lewin's expressive illustrations make the most of this hilarious situation. Come join the fun as a bunch of literate cows turn Farmer Brown's farm upside down. --Publisher's description
Keywords: Cows; Domestic animals; Fiction; Typewriters

No Logo: Taking Aim at the Brand Bullies - Klein, Naomi (Flamingo, 2000)
The hotly debated report from the frontlines of mounting backlash against multinational corporations. A national bestseller, No Logo took Canadians by storm when it was published last year in hardcover. Equal parts cultural analysis, political manifesto, mall-rat memoir, and journalistic exposé, it is the first book to uncover a betrayal of the central promises of the information age: choice, interactivity, and increased freedom. No Logo takes apart our packaged and branded world and puts the pieces into clear pop-historical and economic perspective. Naomi Klein tracks the resistance and self-determination mounting in the face of our new branded world and explains why some of the most revered brands in the world are finding themselves on the wrong end of a bottle of spray paint, a computer hack, or an international anti-corporate campaign. --Publisher's description, Vintage edition
Keywords: Anti-Corporation; Brands; Corporate power; Multinational Corporations; Retail

Les relations du travail au Québec - Leclerc, Michel; Quimper, Michel (Presses de l'Université du Québec, 2000)
Les auteurs décrivent les aspects historiques, légaux et sociaux du Québec et les comparent avec ceux qui prévalent ailleurs. Ils brossent un tableau de la législation du travail, de la vie syndicale, de la négociation collective, de la gestion de la convention collective et de l'avenir des relations du travail. --Publisher's description
Keywords: Collective bargaining; Collective bargaining Québec (Province); Droit du travail; Employee-management relations in government; Employee-management relations in government Québec (Province); Industrial relations; Industrial relations Québec (Province); Labor laws and legislation; Labor laws and legislation Québec (Province); Labor unions; Labor unions Québec (Province); Livres électronique; Législation; Négociation collective; Négociations collectives Québec (Province); Personnel Direction Québec (Province); Personnel management; Personnel management Québec (Province); Québec; Québec (Province); Relations de travail; Relations industrielles Québec (Province); Secteur public; Secteurs public et para-public Relations de travail Québec (Province); Syndicat; Syndicats Québec (Province); Travail Droit Québec (Province)

Men for the Mountains - Marty, Sid (Penguin Random House Canada, 2000)
As a park warden in the national parks of Canada's Rocky Mountains, Sid Marty came to know that beautiful and treacherous landscape as few men or women do. He was a mountain climber, rescue team member, firefighter, wildlife custodian, and adviser to tourists, adventurers, and people passing through. At all times, he was an acute observer of human and animal behaviour. In these pages he records with wry wit and bitter insight true stories of heroism and folly drawn from life in the high country. Marty writes vividly about a land and a way of life that are increasingly endangered. The visceral energy of his prose compels attention. This is a compulsive, alarming, and often hilarious read. --Publisher's description
Keywords: Adventure; Fire Fighter; Humour; Landscape; Mountains; Rescue Team Member; Working with the land

Boys in the Pits: Child Labour in Coal Mines - McIntosh, R. G. (Robert G.) (McGill-Queen's University Press, 2000)
A controversial and chilling examination of child labour in Canadian coal mines, Boys in the Pit shows that beginning early in the nineteenth century, thousands of boys, some as young as eight, laboured underground - driving pit ponies, manipulating ventilation doors, and helping miners cut and load the coal that fuelled the industrial revolution. Boys died in the mines in explosions and accidents but they also organized strikes for better working conditions. Robert McIntosh recasts these wage-earning children as more than victims, illustrating that they responded intelligently and resourcefully to their circumstances. Boys in the Pits is particularly timely as, despite the United Nations Convention on the Rights of the Child, accepted by the General assembly in 1989, child labour still occurs throughout the world and continues to generate controversy. McIntosh provides an important new perspective from which to consider these debates, reorienting our approach to child labour, explaining rather than condemning the practice. Within the broader social context of the period, where the place of children was being redefined as - and limited to - the home, school, and playground, he examines the role of changing technologies, alternative sources of unskilled labour, new divisions of labour, changes in the family economy, and legislation to explore the changing extent of child labour in the mines. --Publisher's description
Keywords: Child labor; Coal miners

Who has Seen the Wind - Mitchell, W. O. (William Ormond) (McClelland & Stewart, 2000)
When W.O. Mitchell died in 1998 he was described as “Canada's best-loved writer.” Every commentator agreed that his best – and his best-loved – book was Who Has Seen the Wind. Since it was first published in 1947, this book has sold almost a million copies in Canada. As we enter the world of four-year-old Brian O’Connal, his father the druggist, his Uncle Sean, his mother, and his formidable Scotch grandmother (“she belshes…a lot”), it soon becomes clear that this is no ordinary book. As we watch Brian grow up, the prairie and its surprising inhabitants like the Ben and Saint Sammy – and the rich variety of small-town characters – become unforgettable. This book will be a delightful surprise for all those who are aware of it, but have never quite got around to reading it, till now. --Publisher's description
Keywords: Drugs; Prairies; Social Class and Equality

The IWA in Canada: The Life and Times of an Industrial Union - Neufeld, Andrew; Parnaby, Andrew (IWA Canada/New Star Books, 2000)
The IWA, while closely linked to BC, has played a crucial role in nearly every province in Canada, from the Queen Charlotte Islands to Grand Falls, Newfoundland. The IWA in Canada is a definitive history of the union that follows its progress and setbacks throughout the past century. Its predecessors, the Industrial Workers of the World, the One Big Union, and the Lumber Workers' Industrial Union are examined, as are the historical tensions between craft and industrial unionism, the drive to organize the "timber beasts", and the pioneering role of communist activists. Today, the legendary militancy of IWA members is being brought to bear on the legalistic negotiations, environmental movements, and evolutions in governmental forest policy that continue to pose challenges. Generously illustrated with historical and present?day photographs, and enriched by numerous interviews with founding unionists, The IWA In Canada also features capsule histories of each local. In-depth analysis of specific issues and events such as the mysterious death of Viljo Rosval and Jon Voutilainen, the fight for relief in the Great Depression and the Loggers' Navy can be found in sidebars that enhance the text throughout. --Publisher's description.
Keywords: Canada; History. Lumbermen; IWA Canada; International Woodworkers of America-Canada; Labor Unions; Labor unions. Woodworkers; Woodworkers

Labouring the Canadian Millennium: Writings on Work and Workers, History, and Historiography - Palmer, Bryan D. (Past CCLH Publications, 2000)
As Canadian workers, the labour movement, and scholars confront a new millennium, new opportunities and new challenges loom large. This volume, which mirrors Labour/Le Travail Volume 46, commissions a number of articles addressing themes that will be of consequence as we enter the 21st century. The articles that appear in this collection are authored by some of the more prominent social scientists working in the field of labour-related studies, among them Desmond Morton, Ian McKay, Joan Sangster, Cynthia Comacchio, David Frank, and Jacques Rouillard. Their writing appears in the book, grouped in a series of thematic sections: institutions and ideas; gender, sexuality and family; Quebec and the national question; culture; and workers and the state. Topics such as Canadian socialism, pivotal events such as the 1949 Asbestos strike, and important cultural undertakings, such as working-class representations on film and video, are addressed. Historiographical controversies and debates associated with the relations of women’s and working-class histories or different generational styles associated with the presentation of labour’s past are surveyed. This is an issue all interested in Canadian society and its development will not want to miss. --Publisher's description
Keywords: Canada; History; History. Labor movement; History. Working class; Labor; Labor movement; Working class

A Memoir of the Spanish Civil War: An Armenian-Canadian in the Lincoln Battalion - Stephens, D. P. (Douglas Patrick) (Past CCLH Publications, 2000)
A Memoir of the Spanish Civil War is one man's bittersweet account of fighting with the International Brigades against the forces of General Francisco Franco in Spain from 1936 to 1939. Douglas Patrick (Pat) Stephens was born in Armenia in 1910 and emigrated with his family to Canada in 1926. Like countless others, his dream of finding a new and more prosperous life was severely shaken by the onset of the Great Depression, and he turned to the Communist Party of Canada in an attempt to combat the political and economic deterioration which had gripped much of the world. Franco's attempt to overthrow by military force the republican government of Spain seemed to Pat Stephens the ideal opportunity to put his political convictions into action. Through his connections in the Communist Party, he became one of some 1400 Canadians, and 40,000 International Volunteers in all, who went to Spain. Many of the volunteers, including the Canadians, went to Spain against the laws and the wishes of their governments. Many of them never came back. Stephens' memoir, dictated to his wife Phyllis Stephens shortly before his death in 1987, puts a very human face on this strange and complex war. It is a portrait of political and moral conviction tinged by creeping disillusionment. It is also a compelling depiction of the strength, frailty, doubt, and courage which can result from the sometimes incongruous intersection of the personal and the political. A Memoir of the Spanish Civil War is a valuable contribution to our understanding of the conflict which immediately preceded World War II, and of Canada's role in that conflict. -- Publisher's description
Keywords: Civil War, 1936-1939; Ejército Popular de la República. Abraham Lincoln Battalion; History; Personal narratives, Canadian; Soldiers; Spain

Temporary Work: The Gendered Rise of a Precarious Employment Relationship - Vosko, Leah F. (Studies in comparative political economy and public policy, 2000)
The first in-depth analysis of temporary work in Canada, this book by Leah F. Vosko examines a number of trends, including the commodification of labour power; the decline of the full-time, full-year job as a norm; and the gendered character of prevailing employment relationships. Spanning the period from the late nineteenth to the late twentieth century, Temporary Work traces the evolution of the temporary employment relationship in Canada and places it in an international context. It explores how, and to what extent, temporary work is becoming the norm for a diverse group of workers in the labour market, taking gender as the central lens of analysis." "Recent scholarship emphasizes that the nature of work is changing, citing the spread of non-standard forms of employment and the rise in women's participation in the labour force. Vosko confirms that important changes are indeed taking place in the labour market, but argues that these changes are best understood in historical, economic, and political context. This book will be invaluable to academics in a variety of disciplines as well as to policy analysts and practitioners in government, industry, and organized labour. --Publisher's descsription
Keywords: 1900-1999; Canada; Canadá; Convenio de la OIT; Division sexuelle du travail Canada Histoire 20e siècle; Estados Unidos; Etats-Unis; Femmes Travail Canada Histoire 20e siècle; History; ILO Convention; ILO Recommendation; Recomendación de la OIT; Sexual division of labor; Sexual division of labor Canada History 20th century; Temporary employment; Temporary employment Canada History 20th century; Travail temporaire Canada Histoire 20e siècle; USA; Women Employment; Women Employment Canada History 20th century; agence de travail temporaire; agence pour l'emploi privée; agencia de empleo privada; collective bargaining; comentario; comment; commentaire; condiciones de empleo; conditions d'emploi; conditions of employment; contrat de travail; contratación; contrato de trabajo; convention de l'OIT; cuadros estadísticos; developed countries; discriminación por razones de sexo; discrimination fondée sur le sexe; division du travail basée sur le sexe; división del trabajo por sexo; domestic worker; empleo temporal; emploi temporaire; employment security; employé de maison; empresa de trabajo temporal; femmes mariées; flexibilidad del trabajo; flexibilité du travail; formación; formation; histoire; historia; history; immigrant; inmigrante; labour contract; labour flexibility; labour force participation; labour legislation; legislación del trabajo; législation du travail; married women; migrant workers; mujeres casadas; negociación colectiva; négociation collective; papel de la OIT; pays développés; países desarrollados; private employment agency; protección social; protection sociale; recommandation de l'OIT; recruitment; recrutement; role of ILO; rôle de l'OIT; salaire; salario; seguridad en el empleo; sex discrimination; sexual division of labour; sindicalización; social protection; statistical table; syndicalisation; sécurité de l'emploi; tableau statistique; tasa de actividad de mano de obra; taux d'activité; temporary employment; temporary work agency; tendance; tendencia; trabajador doméstico; trabajador migrante; trabajadoras; trade unionization; training